The Compliance of Limited Liability Companies to Conduct Annual General Meeting of Shareholders - David Tan; Debby Amellya Zahdjuki (Universitas Internasional Batam, 2023)
The presence of the Company Law in Indonesia is a form of the government's special attention to the Company as one of the pillars of Indonesia's national economic development. Some regulations in the Company Law are recommendations, but some are orders that must be implemented. One of them is the agenda of the Annual General Meeting of Shareholders which is regulated in Article 78 paragraph (2) of the Company Law as a mandatory activity that has been neglected by the closed Companies. The Purposive sampling technique is used in this juridical-empirical research supported by interviews with several companies’ organs. The authors present the results of the research in descriptive form supported by analysis using the theory of legal effectiveness from Soejono Soekanto and the theory of sociological jurisprudence from Eugen Ehrlich. Through this research, the authors found a lack of information received and a low understanding by business actors especially in the obligations of the Annual General Meeting of Shareholders. This makes business actors underestimate the Annual General Meeting of Shareholders. Actually, it has a good influence on the Company in financial transparency and accountability for the performance of the Board of Directors and Board of Commissioners of the Company to shareholders. Government contributions are needed through various relevant institutions, such as the Ministry of Law and Human Rights of the Republic of Indonesia and Notary Public to implement the Annual General Meeting of Shareholders as mandated in the Company Law.